Densidade de plantio na produção de ervilha-de-vagem - Tavares, Ana E. B. [UNESP]; Claudio, Marina T.R.; Nakada-Freitas, Pâmela G. [UNESP]; Cardoso, Antonio I. I. [UNESP] (FapUNIFESP (SciELO), 2016)
The optimization of space in vegetable production is very important to the farmer; sometimes this is the threshold of profit. New arrangements of plants with different provisions seek to maximize production. The objective of this research was to evaluate the productivity of edible pea pods in different planting densities, varying the spacing between holes and the number of plants per hole. The experimental design was randomized blocks, with eight treatments in a factorial scheme 4 × 2 (spacing among holes of 0.2, 0.3, 0.4 and 0.5 m with 1 or 2 plants per hole), representing densities of 20,000 to 100,000 plants/ha for spacing of 1.0 m between rows, with six replications. We evaluated the total production/ha, the marketable production/ha and per plant, and the number of marketable pods/ha and per plant. The data were submitted to the F test, and the means concerning number of plants per hole were compared by Tukey’s test and the spacing between holes by regression analysis. Higher productivity was obtained (15.53 t/ha with 2 plants per hole) and lower production of pods per plant (150 g, with 2 plants per hole), the smaller the spacing (0.2 m). However, if the farmer decides to plant on greater spacing, the density of two plants per hole is recommended.
Plant density in the production of edible pod pea
Keywords: Pisum sativum; Spacing; Yield